Population Genetic Structure and Potential Incursion Pathways of the Bluetongue Virus Vector Culicoides brevitarsis (Diptera: Ceratopogonidae) in Australia - Tay, W. T. (PLoS One, 2016)
Culicoides brevitarsis is a vector of the bluetongue virus (BTV), which infects sheep and cattle. It is an invasive species in Australia with an assumed Asian/South East Asian origin. Using one mitochondrial marker (i.e., part of the cytochrome oxidase subunit I gene) and six nuclear markers, we inferred population genetic structure and possible incursion pathways for Australian C. brevitarsis. Nine mitochondrial haplotypes, with low nucleotide sequence diversity (0.0–0.7%) among these, were identified in a sample of 70 individuals from seven sites. Both sets of markers revealed a homogeneous population structure, albeit with evidence of isolation by distance and two genetically distinct clusters distributed along a north-to-south cline. No evidence of a cryptic species complex was found. The geographical distribution of the mitochondrial haplotypes is consistent with at least two incursion pathways into Australia since the arrival of suitable livestock hosts. By contrast, 15 mitochondrial haplotypes, with up to four times greater nucleotide sequence diversity (0.0–2.9%) among these, were identified in a sample of 16 individuals of the endemic C. marksi (sampled from a site in South Australia and another in New South Wales). A phylogenetic tree inferred using the mitochondrial marker revealed that the Australian and Japanese samples of C. brevitarsis are as evolutionarily different from one another as some of the other Australian species (e.g., C. marksi, C. henryi, C. pallidothorax) are. The phylogenetic tree placed four of the species endemic to Australia (C. pallidothorax, C. bundyensis, C. marksi, C. henryi) in a clade, with a fifth such species (C. bunrooensis) sharing a common ancestor with that clade and a clade comprising two Japanese species (C. verbosus, C. kibunensis).